(untitled) (Studia Prawnicze / The Legal Studies, 2010)
Timesharing, który jest instytucją bardzo rozpowszechnioną, w tym w Hiszpanii, stanowi zarazem oryginalną konstrukcję prawną dotyczącą korzystania z rzeczy (głównie nieruchomości). W drodze umowy timesharingu, określony podmiot (nabywca) uzyskuje prawo do korzystania z rzeczy w oznaczonym czasie w każdym roku oraz zobowiązuje się w zamian do zapłaty wynagrodzenia. Jest to uprawnienie o charakterze periodycznym, polega ono na korzystaniu z nieruchomości w ciągu stosunkowo krótkich odcinków czasu w roku przez wiele lat, szczególnie często dotyczy ono nieruchomości położonych w atrakcyjnych miejscowościach turystycznych. Timeshare purchasing has become an increasingly popular method of holiday planning. Timesharing is generally described and understood by lay purchasers as the purchase of a week or more stay in a recreational or resort property. The purchaser of such a right is entitled to use, occupy and possess the property during those weeks and for the corresponding weeks in subsequent years. Notwithstanding this general understanding of timeshare right by lay purchasers, timesharing presents some unique and interesting problems. This legal and business problems arise because timesharing is a relatively new industry and focuses mainly on time. Timeshare right intends to convert time into a tangible marketable commodity – a commodity sold in fifty-two week slices. This form of holiday planning appeals both to developers and vacationers because of the steady demand for vacation housing and the flexibility offered by this institution. This flexibility can be achieved because purchasers of such a timeshare right may exchange blocks of time with other timeshare purchasers – not only within their own resort, but also with timeshare holiday makers from resorts in other areas and even countries. As the timeshare industry has developed, some particular problems have been identified. Deceptive sales practices, inept management, and a shortage of buyer protection instruments have destroyed the industry’s image and encouraged the public pressure for increased regulation in many European countries and on the European level. As a result, the European Parliament and the Council put forward Directive 94/47/EC of 26 October 1994 on the protection of purchasers in respect of certain aspects of contracts relating to the purchase of the right to use immovable properties on a timeshare basis. Directive 94/47 has been transposed in Spain with Law 42/98 of December 15, on timesharing rights on immovable goods for tourist use and taxation norms. The aim of this article is to present Spanish Law 42/98 of December 15, on timesharing rights on immovable goods for tourist use and taxation norms. The article begins with the reference to the scope of application, the description of the purchaser and the vendor, and the legislative techniques to introduce them. Next, there is a definition of the contracts falling into the scope of Law 42/98 and the basic assumptions of them (the length of time, the payment of a certain global price, a real property right or any other right relating to the use of one or more immovable properties for a specified or specifiable period of the year.) Spanish law differs on one essential point: it establishes two ways of creating the right: a right in rem, or as rent of a house for some seasons under some special conditions. The next part focuses on the consumer protection instruments. Firstly, they are information duties with the information document. The vendor must be required to provide any person asking for information with a document, which contains a general description of the immovable property along with at least brief and accurate information on certain details listed in Law 42/98. Secondly, there are also some obligatory items which the contract must include. Thirdly, reference is made to the requirements with regard to form and language of the information document and the contract, together with the sanctions for non-compliance of them. Fourthly, the right of withdrawal is discussed, that the contract must include information on the right to withdraw from the contract, on the withdrawal period and formal requirements for exercising this right. Fifthly, the issue of prohibition of advance payments before the end of the withdrawal period is addressed. The article also provides some information with regard to private international law. Finally, there is a comparison of the legal solutions adapted in Polish Law transposing directive 94/47 with the solutions offered by Spanish Law. The last part of the article gives an overview of the new directive 2008/122 replacing the directive 94/47 and explains how the new directive differs from the old one.